1996
DOI: 10.1007/bf02437841
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological and demographic study of transsexuals in the Netherlands

Abstract: This is an epidemiological and demographic study of 1285 transsexuals in the Netherlands. The data were collected from 1975 to the end of 1992. Over 95% of the Dutch transsexuals have been treated at the study center. Between 1975 and 1984 the annual number of female-to-male transsexuals increased, stabilizing thereafter. In the male-to-female transsexuals this trend continued up to 1989, declining slightly thereafter. Over the last 5 years on average 50 (range 38-60) male-to-female transsexuals and 21 (range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
62
0
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(76 citation statements)
references
References 13 publications
9
62
0
5
Order By: Relevance
“…In the following two decades the ratio remained at about 2.5:1 (so far few ®gures are available from the 1990s). A recent study tends to con®rm this ®gure for Holland (1). Other investigations in past years found the ®gures for the two sexes even closer (2±5, 7).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In the following two decades the ratio remained at about 2.5:1 (so far few ®gures are available from the 1990s). A recent study tends to con®rm this ®gure for Holland (1). Other investigations in past years found the ®gures for the two sexes even closer (2±5, 7).…”
Section: Discussionmentioning
confidence: 69%
“…In fact, the only reliable ®gures available, taken from large samples observed over a long period of time, come from Sweden and Holland. While in Holland the sex ratio has remained more or less stable at 3:1 for many years (1), more recent research in Sweden has shown a smaller difference between the sexes of about 1.4:1 (2,3). Findings from the United States (4,5), Canada (6) and Belgium (7) con®rm that transsexualism is being found increasingly almost equally frequently in both sexes.…”
Section: Introductionmentioning
confidence: 98%
“…La prevalencia estimada de transexualidad es variable según el sexo biológico; en base a diferentes estudios europeos, aproximadamente 1 de cada 11.900 varones adultos son transexuales femeninos y 1 de cada 30.400 mujeres adultas son transexuales masculinos 6,7 . Según estas prevalencias, y teniendo en cuenta que en Navarra había censados (en 2011) 320.656 varones y 321.395 mujeres, se estima una prevalencia en Navarra de 27 transexuales femeninas y 11 transexuales masculinos aproximadamente 8 .…”
Section: Discussionunclassified
“…The prevalence of transsexualism as assessed in The Netherlands and based on numbers of people seeking sex reassignment, is 1 : 11 900 men and 1 : 30 400 women. 9 These figures are very stable. They are somewhat lower than those of Singapore but higher than those in Sweden.…”
Section: Transsexualism/the Subjective Experiencementioning
confidence: 92%
“…9 For instance, in Serbia, the ratio is close to 1 : 1, 11 and in Japan 1 : 2. 10 There is no good explanation for this sex difference, neither for the geographical variation.…”
Section: Transsexualism/the Subjective Experiencementioning
confidence: 96%